2008
DOI: 10.1111/j.1365-2656.2008.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating patterns and processes of demographic variation: environmental correlates of pre‐breeding survival in red‐billed choughs Pyrrhocorax pyrrhocorax

Abstract: Summary 1.Quantifying the pattern of temporal and spatial variation in demography, and identifying the factors that cause this variation, are essential steps towards understanding the structure and dynamics of any population. 2. One critical but understudied demographic rate is pre-breeding survival. We used long-term colour-ringing data to quantify temporal (among-year) and spatial (among-nest site) variation in pre-breeding survival in red-billed choughs ( Pyrrhocorax pyrrhocorax ) inhabiting Islay, Scotland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 51 publications
1
56
0
Order By: Relevance
“…Only six ringed individuals have been observed to disperse between Islay and Colonsay in over twenty years (although Colonsay was probably colonised from Islay in the late 1960s, Reid et al 2003Reid et al , 2008. Nevertheless, field observations show that choughs do occasionally disperse over long distances.…”
Section: Genetic Structure and Dispersalmentioning
confidence: 99%
See 2 more Smart Citations
“…Only six ringed individuals have been observed to disperse between Islay and Colonsay in over twenty years (although Colonsay was probably colonised from Islay in the late 1960s, Reid et al 2003Reid et al , 2008. Nevertheless, field observations show that choughs do occasionally disperse over long distances.…”
Section: Genetic Structure and Dispersalmentioning
confidence: 99%
“…This work has identified intrinsic and extrinsic constraints on population growth rate (e.g. Blanco et al 1998a;Kerbiriou et al 2006;Reid et al 2004Reid et al , 2006Reid et al , 2008, and highlighted the key role of human impacts in the chough's decline, involving historic persecution (Monaghan 1988;Carter et al 2003), contemporary tourism pressure (Kerbiriou et al 2009) and agricultural land-use change (Blanco et al 1998b;Whitehead et al 2005;Kerbiriou et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that this relationship remained significant despite these caveats, and the lack of accounting for other processes known to affect upland birds (Pearce-Higgins et al 2009a), suggests that it is worthy of further investigation. The negative correlation between ring ouzel population change and summer temperature (Beale et al 2006), and limiting effects of tipulid abundance on the survival of first-year chough Pyrrhocora pyrrhocorax, another tipulid specialist, supports this contention (Reid et al 2008). Detailed work replicating the approach of Pearce-Higgins et al (2010) on a wider range of species -particularly, dunlin Calidris alpina, whimbrel, ring ouzel and snow bunting, which are all declining -should therefore be conducted to test whether this correlation is causative.…”
Section: Relationship Between Diet and Upland Bird Population Trendsmentioning
confidence: 82%
“…Similarly, Cam et al (2003) found evidence of long-term consequences of the length of the rearing period on reproductive success after recruitment in Kittiwakes. Reid et al (2003Reid et al ( , 2008 also found evidence of a relationship between early cohort conditions and future breeding success in Choughs (Pyrrhocorax pyrrhocorax), or between natal location and adult survival. In other words, there is substantial heterogeneity in results according to the species, study design and methods used to collect or analyze data.…”
Section: Long-lived Speciesmentioning
confidence: 98%